The larva of Psilopteryx psorosa (Kolenati 1860) (Trichoptera: Limnephilidae) with notes on ecology and zoogeography - Waringer, Johann; Graf, Wolfram; Malicky, Hans (Zootaxa, 2013)
The paper gives a description of the hitherto unknown larva of Psilopteryx psorosa (Kolenati 1860), subspecies bohemosaxonica Mey & Botosaneanu 1985 (Trichoptera: Limnephilidae: Limnephilini, Chaetopterygina; Vshivkova et al. 2007). Information on the morphology of the larva is given and the most important diagnostic features are illustrated. In the context of already available keys, the larva of P. psorosa bohemosaxonica keys together with Pseudopsilopteryx zimmeri (McLachlan 1876), Chaetopteryx fusca Brauer 1857 and C. villosa (Fabricius 1798). Psilopteryx psorosa is not yet separable from P. zimmeri but may be easily separated from the two Chaetopteryx species by the median fusion of setal groups sa1 at the first abdominal sternum in P. psorosa which is lacking in C. fusca and C. villosa. With respect to distribution, P. psorosa bohemosaxonica is present in the Bohemian Forest and the Erzgebirge (Upper Austria, Czech Republic, and Germany). In addition, ecological characteristics are briefly discussed.